Model for a transcript map of human chromosome 21: isolation of new coding sequences from exon and enriched cDNA libraries. - Yaspo, M; Gellen, L; Mott, R; Korn, B; Nizetic, D; Poustka, A; Lehrach, H (1995)
The construction of a transcriptional map for human chromosome 21 requires the generation of a specific catalogue of genes, together with corresponding mapping information. Towards this goal, we conducted a pilot study on a pool of random chromosome 21 cosmids representing 2 Mb of non-contiguous DNA. Exon-amplification and cDNA selection methods were used in combination to extract the coding content from these cosmids, and to derive expressed sequences libraries. These libraries and the source cosmid library were arrayed at high density for hybridisation screening. A strategy was used which related data obtained by multiple hybridisations of clones originating from one library, screened against the other libraries. In this way, it was possible to integrate the information with the physical map and to compare the gene recovery rate of each technique. cDNAs and exons were grouped into bins delineated by EcoRI cosmid fragments, and a subset of 91 cDNAs and 29 exons have been sequenced. These sequences defined 79 non-overlapping potential coding segments distributed in 24 transcriptional units, which were mapped along 21q. Northern blot analysis performed for a subset of cDNAs indicated the existence of a cognate transcript. Comparison to databases indicated three segments matching to known chromosome 21 genes: PFKL, COL6A1 and S100B and six segments matching to unmapped anonymous expressed sequence tags (ESTs). At the translated nucleotide level, strong homologies to known proteins were found with ATP-binding transporters of the ABC family and the dihydroorotase domain of pyrimidine synthetases. These data strongly suggest that bona fide partial genes have been isolated. Several of the newly isolated transcriptional units map to clinically important regions, in particular those involved in Down's syndrome, progressive myoclonus epilepsia and auto-immune polyglandular disease. The study presented here illustrates the complementarity of exon-amplification and cDNA selection techniques for generating a large resource of new expressed landmarks, which contribute to the construction of a chromosome 21 transcript map.